Ghetto o cruzada: deslaicizar la laicidad - Arboleda Mora, Carlos (Veritas, 2013)
This article has as aim show what is a healthy secularism in the current pluralist, multicultural, democratic and diverse society. First, it presents two temptations of the church today: to shelter in the ghetto and to be closed to the world giving reason to the lay fundamentalists who consider faith to be something private, or to go out to the crusade to impose Christian beliefs and message. Then there is analyzed the historical process of formation of the pluralism, of the secularism and of the religious freedom emphatically in the models North American and French. The article concludes with a vision of what is the secularism in the doctrine of the catholic church today and a proposal of what must be the real pluralism and the healthy secularism today.